2014
DOI: 10.3171/2014.1.peds13490
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic olivary degeneration in a child following midbrain tumor resection: longitudinal diffusion tensor imaging studies

Abstract: Hypertrophic olivary degeneration (HOD) is a dynamic process caused by disruptive lesions affecting components of the Guillain-Mollaret triangle (GMT). The authors applied diffusion tensor imaging (DTI) to investigate longitudinal changes of the GMT components in a child with HOD after neurosurgery for a midbrain tumor. Diffusion tensor imaging data were acquired on a 1.5-T MRI scanner using a balanced pair of diffusion gradients along 20 noncollinear directions 1 day and 3, 6, and 9 months after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…In addition, the increase of the MD implies a general increase in diffusion and can be explained through a decrease in cell density, either caused by cell death or extracellular edema ( 42 ). Both findings are largely in line with previous DTI studies of HOD ( 21 , 29 , 31 ) and correspond well to the histopathological findings in HOD ( 9 , 10 ). This supports the prior assumption that high differences of PD-w intensity in the left and right anterior quadrant of the medulla oblongata indeed indicate the presence of HOD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the increase of the MD implies a general increase in diffusion and can be explained through a decrease in cell density, either caused by cell death or extracellular edema ( 42 ). Both findings are largely in line with previous DTI studies of HOD ( 21 , 29 , 31 ) and correspond well to the histopathological findings in HOD ( 9 , 10 ). This supports the prior assumption that high differences of PD-w intensity in the left and right anterior quadrant of the medulla oblongata indeed indicate the presence of HOD.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies assessed diffusion-weighted methods such as diffusion tensor imaging (DTI) in HOD patients. As the main finding, one study found a non–significant decrease in fractional anisotropy (FA) and a significant increase in diffusivity of the ION in HOD patients compared with controls ( 21 ), which is in line with previous case reports ( 29 31 ).…”
Section: Introductionsupporting
confidence: 88%
“…The potential utility of advanced MRI techniques has been explored in HOD. For example, Orman et al reported the use of DTI in a 14‐year‐old boy with HOD after resection of a midbrain pilocytic astrocytoma and showed that in the affected inferior olivary nucleus, there was initial decrease in FA and increase in mean, axial, and radial diffusivities during the first 3 months, followed by increase in FA and decrease in diffusivities after 3 months . Another example is utilizing susceptibility‐weighted imaging (SWI) in children with HOD after posterior fossa tumor resection to demonstrate degeneration of the red nucleus, with loss of the normal hypointensity of red nucleus on SWI from normal iron deposition .…”
Section: Brainstem and Cerebellar Neural Networkmentioning
confidence: 99%
“…DTI has been used to diagnose the condition of HOD with increased radial and axial diffusivity and decreased fractional anisotropy (FA) in the affected inferior olivary nucleus. 10 Use of DTI also has been described for demyelination-induced HOD. 11 To our knowledge, this is the first reported case of TDI being used to support a clinical diagnosis of HOD secondary to a demyelinating lesion.…”
Section: Discussionmentioning
confidence: 99%